Diet-regulated transcriptional plasticity of plant parasites in plant–mutualist environments - M. Willow H. Maxwell; Barry E. Causier; Jasper Chippendale; James R. Ault; Chris A. Bell (Proceedings of the National Academy of Sciences, 2025)
Crop pathogens often lack exclusive access to their host and must interact with plants concurrently engaged with numerous other symbionts. Here, we demonstrate that the colonization of hosts by plant–mutualistic mycorrhizal fungi can indirectly induce transcriptional responses of a major plant parasite, the nematode Globodera pallida , via a modified host resource profile. A shift in the resource profile of the root, where the parasite feeds, is perceived and responded to by the parasite through transcriptional changes, potentially to optimize resource intake. Specifically, G. pallida react to reduced host-photosynthate influx due to concurrent mycorrhizal-host symbiosis by upregulating the expression of a sugar transporter ( SWEET3 ) in the nematode intestine. We identify this gene’s role in parasite growth and development, regulated by the putative diet-responsive transcription factor Gp-HBL1. Overall, our data unveil a mechanism by which a parasitic animal responds to fluctuations in host plant quality that is induced by a plant–mutualistic fungus, to enhance parasitism and reproduction.